Peran Suwarni Pringgodigdo dalam Pergerakan Perempuan di Indonesia Tahun 1926-1967 (DIAKRONIK: Jurnal Pemikiran dan Penelitian Sejarah, 2025)
This study examines the family background and education of Suwarni Pringgodigdo, as well as her role in the Indonesian women's movement from 1926 to 1967. Using the historical method, which includes heuristics, source criticism, interpretation, and historiography, this research finds that Suwarni's privileged family background and education enabled her to become a key figure in several women's organizations. She began her activism in Jong Java Meisjeskring Bogor and Putri Indonesia Bandung, later founding and leading Istri Sedar. After Indonesian independence, Suwarni continued her efforts by participating in national politics and advocating for women's rights. The findings indicate that Suwarni Pringgodigdo's contributions were fundamental in advancing the position of women in Indonesia and show that the women's movement is inseparable from the broader national movement.